Impacts of typical pharmaceuticals and personal care products on the performance and microbial community of a sponge-based moving bed biofilm reactor. (January 2020) - Zhang, Xinbo; Song, Zi; Hao Ngo, Huu; Guo, Wenshan; Zhang, Zumin; Liu, Yang; Zhang, Dan; Long, Zhongliang
Graphical abstract: Highlights: MBBR reactor is a viable treatment to removal typical PPCPs. High concentration PPCPs exhibited significant inhibiting effect on nitrogen removal. Increasing PPCPs concentration properly (<2 mg/L) could increase microbial diversity. Different types and concentrations PPCPs altered microbial community greatly. Abstract: Four lab-scale moving bed biofilm reactors (MBBRs) were built to treat simulated wastewater containing typical pharmaceuticals and personal care products (PPCPs). The efficiency in removing different PPCPs at different concentrations (1, 2 and 5 mg/L) and their effects on the performance of MBBRs were investigated. Results showed that the average removal efficiencies of sulfadiazine, ibuprofen and carbamazepine were 61.1 ± 8.8%, 74.9 ± 8.8% and 28.3 ± 7.4%, respectively. Compared to the reactor without PPCPs, the total nitrogen (TN) removal efficiency of the reactors containing sulfadiazine, ibuprofen and carbamazepine declined by 21%, 30% and 42%, respectively. Based on the microbial community analysis, increasing the PPCPs concentration within a certain range (<2 mg/L) could stimulate microbial growth and increase microbial diversity yet the diversity reduced when the concentration (5 mg/L) exceeded the tolerance of microorganisms. Furthermore the presence and degradation of different PPCPs resulted in a different kind of microbial community structure in the MBBRs.